Local economic development strategies in a medium-sized city on the European periphery: a path to become an economic center of Eastern Central Europe importance - Kozma, Gábor; Saidi, Feyrouz Ahlam; Molnár, Ernő (Frontiers in Political Science, 2024)
Large cities are becoming increasingly valuable in the spatial structure of globalized economies. Although these centers vary significantly regarding population, economic structure, and income conditions, they—compared to their surroundings—generally show a higher productivity level, a higher rate of employment, higher education, and higher innovation performance. However, this metropolization and concentration of the economy in large cities made the development of cities regarded as medium-sized on an international scale an issue of competitiveness in Europe, characterized by dense town networks, a small number of metropolises, and a significant weight of medium- and small-sized towns. However, one of the main preconditions for achieving success in this competition is to form a comprehensive and complex concept with a significant emphasis on economic development. Therefore, the aim of our study is to analyze the local economic development strategies for the last three decades, as elaborated in Debrecen. In the framework of our empirical analysis, we examined how different mainstream concepts appear in local development strategies and which development objectives are determined by the local strategies. Furthermore, we also aimed to identify possible changes in ideas about city roles by referring to the organization of economic space.